The Editorial Eye: Focusing on Publications Standards, Practices, and Trends - Deborah B. Witham (Journal of Applied Communications, 1999)
A review of The Editorial Eye: Focusing on Publications Standards, Practices, and Trends, published monthly by EEI Press, editor: Linda B. Jorgensen. NOTE: only page 1 of the review is available.